Duration dependence as an unemployment stigma: Evidence from a field experiment in Germany - Patrick Nüß (Kiel University, Department of Economics, 2018)
Based on a correspondence experiment covering 3,124 fictitious job applications, the paper identifies and quantifies duration dependence in Germany, with a particular emphasis on company and vacancy characteristics as potential determinants. The experiment reveals that duration dependence manifests itself in a sharp decline of 26% to 35% in callbacks when an individual has been unemployed for 10 months, pointing to the existence of an unemployment stigma for Germany. The results are driven by labor market tightness, companies' access to applicants and screening behavior related to company size, with no evidence for an unemployment stigma determined by the contract type.
Keywords: C93; J68; J23; J64; J71; 330; Field Experiments; Public Policy; Labor Demand; Unemployment Duration; Labor Discrimination